Forecasting and analysis of energy consumption - Товма, Н.; Тлеппаев, A. (Journal of Economic Research & Business Administration, 2017)
Prediction – powerful statistical power management tools in the industry. In this article we examined two complementary statistical forecasting models: the corridor for a few months in advance and a model for a day ahead. The basis of the energy-saving is the systematic implementation of a wide range of technical and technological measures to be implemented in the framework of an optimal power consumption infrastructure management procedures at the system level. Energy savings can be achieved by improving the activity of the administrative apparatus. This article presents the results of the implementation of energy forecasting model, which reduces energy consumption as a whole by more than 20%. Prediction may be performed based on a static model that reflects the process of power consumption for the year ahead. Dynamic stochastic modeling allows the forecast for the medium term (5 - 7 years). The main advantage of this approach – is the formation of a fair rate of energy expenditure, taking into account fuel quality, as well as the current state of energy consumption.